Investigating the Effect of Water Velocity on Savonius Water Rotor - Abadi, Reza Perdana; Wihadi, Dwiseno (Institut Teknologi Dirgantara Adisutjipto, 2018)
Energy can be obtained from the flow of water in irrigation channels. Savonius water rotor can be applied to low velocity flow and does not cause substantial losses. Rotor Savonius, which has good initial spinning ability, will assist in its operations. The experimental study conducted in this paper aims to investigate the effect of water velocity on the performance of the model of Savonius water rotor. The experiments used 2 blades Savonius rotor to show tip speed ratio, torque and power coefficient related with water velocity. The results of study showed that, increased velocity of water flow increases the ability of Savonius water rotor. The Savonius rotor can produce a high power coefficient at low water flow rates when a deflector is added